Personal characteristics and hedonic shopping orientation on apparel adult shoppers' repatronage behavioral intention - Wong, Yue Teng; Osman, Syuhaily (International Foundation for Research & Development, 2013)
A new direction of consumer centric marketing is now advocated to be included in the marketing module, yet there is a lack of shopping repatronage research based on a solid theoretical background pertinent to the issue. Based on the Reasoned Action Approach by Fishbein and Ajzen (2010), this study endeavors to examine the relationships between the personal characteristics, hedonic shopping orientation and repatronage behavioral intention. The structural equation modeling was used to analyze the causal relationships for the self-administrated data gathered from 569 apparel adult shoppers aged 30 to 60 years old. The refined hypothesized model was relatively good fitted. The personal characteristics of need for activity, impulsiveness, shopping confidence and susceptibility to influence were found significantly related to the repatronage behavioral intention. These relationships were fully mediated by the intervening variable of hedonic shopping orientation. The hypothesized model of hedonic mediating structural model explained 56% of the repatronage behavioral intention. The study advanced the understanding of the importance of hedonic shopping orientation as well as the personal characteristics in consumer-centric marketing.